2016
DOI: 10.1016/j.neuro.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to a Mn/Zn ethylene-bis-dithiocarbamate fungicide leads to mitochondrial dysfunction and increased reactive oxygen species production in Caenorhabditis elegans

Abstract: Mn/Zn ethylene-bis-dithiocarbamate (Mn/Zn-EBDC) fungicides are among some the most widely-used fungicides in the world. Although they have been available for over 50 years, little is known about their mechanism of action in fungi, or their potentially toxic mechanisms in humans. To determine if exposure of Caenorhabditis elegans (C. elegans) to a representative fungicide (Manzate; MZ) from this group inhibits mitochondria or produces reactive oxygen species (ROS), we acutely (30 min) exposed worms to various M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Studying whole nematodes, Fitsanakis and colleagues showed that Mn ++ exposure led to defective mitochondrial complex I function, with an increase in hydrogen peroxide concentrations (Bailey et al 2016;Todt et al 2016). In response to the increase in hydrogen peroxide, the expression of a glutathione S-transferase reporter (Pgst-4::gfp) was also increased in the exposed animals.…”
Section: Toxicologymentioning
confidence: 99%
“…Studying whole nematodes, Fitsanakis and colleagues showed that Mn ++ exposure led to defective mitochondrial complex I function, with an increase in hydrogen peroxide concentrations (Bailey et al 2016;Todt et al 2016). In response to the increase in hydrogen peroxide, the expression of a glutathione S-transferase reporter (Pgst-4::gfp) was also increased in the exposed animals.…”
Section: Toxicologymentioning
confidence: 99%
“…Protocols for synchronization, treatment, and endpoint assays used in our lab were previously published in detail (Bailey et al , 2016; Todt et al , 2016). Briefly, C. elegans were grown at 20°C on 8P plates (51.3 mM NaCl, 25.0 g bactoagar/L, 20.0 g bactopeptone/L, 1 mM CaCl 2 , 500 µM KH 2 PO 4 (pH 6), 13 µM cholesterol (95% ethanol), and 1 mM MgSO 4 ) with a lawn of NA22 E. coli (grown in 16 g tryptone/L, 10 g yeast extract/L, 85.5 mM NaCl) until gravid.…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
“…All endpoint assays have been previously described in detail (Todt et al , 2016). Briefly, all treatment groups were standardized to yield 10,000 live worms/mL/treatment concentration.…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This condition may lead to oxidative damage to biomolecules such as proteins, lipids, and nucleic acids [ 9 ] and is implicated in the etiology of several diseases, such as tumors and neurodegenerative disorders [ 10 12 ]. A possible cause of the increment of ROS levels by MZ is the inhibition of the mitochondrial complexes activity, resulting in an inefficient transfer of electrons, leading to the formation of oxygen radicals [ 13 , 14 ]. Also, induction of NADPH oxidase and xanthine oxidase by MZ leading to augmented H 2 O 2 has been reported [ 15 ], and modulation of antioxidant enzyme activity, as published recently by our research group, has been reported in carp brain [ 16 ].…”
Section: Introductionmentioning
confidence: 99%